The method for high order modes parameters estimation in periodical structures - Paramonov, V.V.; Denisenko, D.V. (Вопросы атомной науки и техники, 2012)
The High Order Modes (HOM) parameters are calculated in traveling wave mode at one structure period for the reference set of the phase advance values, with real 3D geometry in the wide frequency range. For the structure with arbitrary length HOM parameters are interpolated basing on periodicity properties. The method resolution doesn’t depends on the number of periods in the structure and allows reliably identify interesting and important HOM parameters for long structures and in high frequency region.